Evaluation of the efficiency in delivery of government services to ameliorate the COVID-19 pandemic in the King Cetshwayo District in South Africa: Recipients’ perspectives - S. Zhou; R. Utete (Cogent Social Sciences)
The COVID-19 pandemic raised the need for an increase in public services to counter the negative economic ramifications of the pandemic. However, this meteoric emergence of coronavirus inadvertently gave birth to inefficiencies entrenched in the delivery of government interventions to contain the disease and its economic effects. The purpose of this paper is to investigate the efficiency in delivery of government services and interventions aimed at ameliorating the COVID-19 pandemic. This study uses descriptive statistics and ordinal regression analysis to identify the drivers of inefficiency perceptions among recipients of social security interventions during the pandemic. Survey data for a sample of 855 participants was drawn from King Cetshwayo District municipality in KwaZulu Natal, South Africa. The key findings revealed that the delivery of most government interventions in South Africa was perceived as not well coordinated and poorly communicated, hence inefficient. Drivers of these perceptions included age, income level, race, and employment status. In addition, whether or not an individual had received some form of social security assistance during the pandemic also influenced their perceptions about government efficiency in providing social security support. We recommend strengthening monitoring and evaluation mechanisms across government service delivery initiatives and improving communication of government programs to improve user experience and access.